Interleukin-41: a novel serum marker for the diagnosis of alpha-fetoprotein-negative hepatocellular carcinoma - Li, Yazhao; Wang, Haoyu; Ren, Danfeng; Li, Jingyu; Mu, Zihan; Li, Chaoyi; He, Yongchao; Zhang, Jiayi; Fan, Rui; Yin, Jiayuan; Su, Jiaojiao; He, Yinli; et al. (Frontiers in Oncology, 2024)
Background For the lack of effective serum markers for hepatocellular carcinoma(HCC) diagnosis, it is difficult to detect liver cancer and identify its recurrence early. Methods Databases were used to analyze the genes potentially associated with alpha-fetoprotein(AFP). ELISA assay was used to detect the serum IL-41 in HCC, liver metastases, hepatitis, and healthy people. Immunohistochemical staining was used to analyze the relative quantification of IL-41 in HCC and paracancer tissues. Various survival curves were plotted according to clinical pathological data and helped us draw the ROC curve of IL-41 diagnosis of HCC. Results The serum expression of IL-41 was highest in AFP negative HCC patients and significantly higher than that in AFP positive HCC and metastatic cancer patients. There was a significant negative correlation between elevated serum IL-41 and AFP(<1500ng/ml). The clinicopathological features suggested that the serum IL-41 level was significantly correlated with capsule invasion, low differentiation and AFP. High serum expression of IL-41 suggests poorer survival and earlier recurrence after resection, and IL-41 upregulated in patients with early recurrence and death. The expression of IL-41 was higher in HCC tissues of patients with multiple tumors or microvascular invasion. The ROC curve showed that serum IL-41 had a sensitivity of 90.17 for HCC and a sensitivity of 96.63 for AFP-negative HCC, while the specificity was higher than 61%. Conclusion IL-41 in serum and tissue suggests poor prognosis and postoperative recurrence in HCC patients and could be a new serum diagnostic marker for AFP negative patients.